Nutrition Counseling for Adolescents with Chronic Energy Deficiency - Jayadi, Yusma Indah; Syahrir, Sukfitrianty; Nurfatmi, Rezki; Achmad, Pratiwi Maharani; Warda, Warda; Putri, Herlin Sagitha (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Chronic Energy Deficiency (CED) is a condition arising from insufficient food intake, leading to chronic health issues. Among adolescent girls, factors such as body image concerns and dietary habits contribute to the development of CED. This study aimed to examine variations in students' intake, knowledge, attitudes, and behaviors before and after receiving nutritional counseling at Private Madrasah Aliyah Alauddin. Employed a pre-experimental design with a one-group pretest-posttest approach, the study involved 49 subjects. Data analysis included univariate tests, normality tests, as well as paired t-tests and wilcoxon tests. The findings indicated that nutritional counseling had a positive impact on subjects’ knowledge and behaviors, though no significant changes were observed in attitudes and dietary intake. The results emphasized the importance of regulating dietary habits. Additionally, the study suggests that, as a follow-up to nutritional counseling, students should actively engage in peer counseling initiatives for adolescents within the school community.